Esperando Ulisses: o mito de Penélope à luz da comparação diferencial e discursiva - Campelo, Janeide Maia (2014)
From the many weavers known, the Queen of Ithaca is certainly among the most famous.Over the years,many writers have dedicated themselves to retell the myth of Penelope in their works by their own way. According to Ute Heidmann, the modern writers recurrence to the Greek myths in order to produce their texts is a renewing discursive practice, which gives new writing and relevance to the myth. (2003, p.47). This work deals with a differential and discursive comparative analysis on the myth of Penelope linking it with two short stories from Brazilian authors: Penélope by João do Rio (1919) and Penélope by Dalton Trevisan (1959). In order to do it, we are supported by: the works of Heidmann (2003, 2006, 2008) and Maingueneau (2006). We also concentrate ourselves on the temporal trace presented in both Penelope s myth and in its modern rewriting so that we can identify how each configuration of the classical myth develops into one of the most celebrated acts of this myth: the waiting. In order to so, we seek support on the studies by Paul Ricoeur (2006), Hans Meyerhoff (1976) and Benedito Nunes (1988)